Study protocol of the HessenKohorte2042: a prospective, longitudinal cohort study characterising quality of life in people with Parkinson’s disease and their caregivers using a bio-psycho-social approach - Lars Timmermann; Heidrun Golla; Christiane Woopen; Petra Ina Pfefferle; Urs M Nater; David José Pedrosa; Urs Kleinholdermann; Franziska Thieken; Marina Christine Ruppert-Junck; Marlena van Munster; Anna Julia Pedrosa; Johanne Stümpel; et al. (BMJ Open)
Introduction Quality of life (QoL) is of paramount importance as an outcome to monitor and guide therapies for people with Parkinson’s disease (PwPD). In particular, due to the heterogeneous symptoms that PwPD may experience during their disease course, QoL can deteriorate not only in patients but also in their caregivers, with a variety of psychosocial consequences. However, there is a lack of longitudinal studies that explore how QoL evolves over time and what factors are significant. Furthermore, holistic approaches that consider bio-psycho-social determinants are rare. In the worst cases, these gaps can lead to suboptimal care and therefore unmet needs for patients and their caregivers, resulting in unnecessary symptom burden and increased healthcare costs for society.Methods and analysis This prospective, longitudinal study will follow 1000 PwPD along with their caregivers for 20 years, with up to 40 semi-annual assessments. Patient data and sample collection will include clinical assessments, self-reported outcome measures focusing on QoL, biospecimen collection and MRI. Caregiver burden will be systematically assessed through self-administered questionnaires. The use of digitised surveys will allow efficient data collection and convenient assessment at home. Our primary objective is to attain a holistic understanding of QoL in PwPD and establish a tool to measure it. The secondary objective is to explore the psycho-social and biological variables associated with QoL of patients and caregivers over the progression of the disease. This will provide key information for diagnostic and prognostic prediction, therapeutic patient stratification and adaptation of therapy in the future.Ethics and dissemination The study was approved by the local ethics committee of the University Hospital of Marburg (study number: 209/19). The results will be disseminated by means of publication in peer-reviewed journals, international conference contributions, annual patient meetings and a dedicated website.Trial registration number German Clinical Trials Register (DRKS00023598).